The Effect of Perceived Risks towards Purchase Intention on Shopee Bandar Lampung - Agustina, Yenny; Hapsari, Putri Syania Awidiya; Wibaselppa, Anggawidia (Proceeding International Conference on Information Technology and Business, 2023)
Over the past few decades, the improving in the market world in Indonesia are changes. Especially in this digitalera, markets tend to be changed from conventional market to modern market. Everything became so simple, for example from using money to e-money and from needing place to needing smart phone only. Nowadays, people are using their smartphone to buy something via online because it is the simplest way. In order to compete with competitors, the company must increase its competitiveness, especially in maximizing customers trust to maximizing the purchase intention. This study aims to explore the trust perception of Shopee and their relationships with Purchase Intention. It provides insight as to what dimension of trust would deliver the best result of Purchase Intention. This research used purposive sampling method in accordance with certain criteria. The questionnaire distributed to 220 respondents via online. Multiple regression analysis and hypothesis testing in partial (t-test) were conducted. The result obtained from this research analysis indicated that dimensions among trust have the positive and significant contributing factors to the enlargement of Shopee purchase intention.Keywords— Trust, Purchase Intention, Perceived Risks